ISO 9001:2015 quality management system design for wooden pallet manufacturing using system entity analysis and BPMN 2.0 - Aster Aryati Rakhmasari; Fajar Ciputra Daeng Bani; Muhammad Zulfan Abdusyakur; Indrani Dharmayanti; Maryadi Tirtana Siregar (Universitas Sultan Ageng Tirtayasa, 2026)
The wooden pallet industry plays a critical role in logistics and supply chain management, yet many companies lack standardized quality management practices, leading to high variability in product quality and order rejections. Although ISO 9001:2015 provides a widely recognized framework for quality management, prior studies have mostly addressed general implementation, with limited focus on industry-specific challenges. This study fills this gap by designing a comprehensive quality management system (QMS) tailored for the wooden pallet sector, integrating system entity analysis and business process modeling (BPMN 2.0) to establish standardized procedures aligned with ISO 9001:2015. A case study of a wooden pallet manufacturing company demonstrates the framework’s potential to improve process standardization, resource utilization, and organizational competitiveness. The proposed QMS serves as a practical roadmap for industry adoption, enhancing quality consistency and operational efficiency. Future research should validate the framework across multiple organizations to confirm its generalizability and effectiveness.